The post-reform guide to derivatives and futures - Peery, Gordon F. (Hoboken, N.J. : Wiley, 2012)
"An in-depth look at the best ways to navigate the post-reform world of derivatives and futuresThe derivatives market is one of the largest, and most important financial markets in the world. It's also one of the least understood. Today we are witnessing the unprecedented reform and reshaping of this market, and along with these events, the entire life cycle of a derivatives transaction has been affected. Accordingly, nearly all market participants in the modern economy need to view the handling of risk by derivatives in a very different way. Many aspects of financial services reform are based on a belief that derivatives caused the Great Recession of 2008. While the difficulties we now face cannot be blamed solely on derivatives, the need to understand this market, and the financial products that trade within it, has never been greater. The Post-Reform Guide to Derivatives and Futures provides straightforward descriptions of these important investment products, the market in which they trade, and the law that now, after July 16, 2011, governs their use in America and creates challenges for investors throughout the world. Author Gordon Peery is an attorney who works exclusively in the derivatives markets and specializes in derivatives and futures reform and market structure. Since representing clients in Congressional hearings involving Enron Corp., he has developed extensive experience in this field. With this guide, he reveals how derivatives law, and market practice throughout the world, began to change in historic ways beginning in 2011, and what you must do to keep up with these changes. Explains what derivatives and futures are, who trades them, and what must be done to manage risk in the post reform world Accurately reflects the futures and derivatives markets as they exist today and how they will be transformed by the Dodd-Frank Wall Street Reform and Consumer Protection Act Highlights the risks and common disputes regarding derivatives and futures, and offers recommendations for best practices in light of the evolving law governing derivatives The financial crisis has changed the rules of Wall Street, especially when it comes to derivatives and futures. The Post-Reform Guide to Derivatives and Futures will help you navigate this evolving field and put you in a better position to make the most informed decisions within it"--
Part I. The Crises That Led to Derivatives Reform -- Part 2. Derivatives Reform -- Part 3. Trading Before and After Reform -- Part 4. Continuing Education.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Derivative securities -- United States; Derivative securities -- Government policy -- United States; Futures -- United States; Futures -- Government policy -- United States; Global Financial Crisis, 2008-2009.; Derivative securities -- Government policy -- United States; Derivative securities -- United States; Futures -- Government policy -- United States; Futures -- United States; Global Financial Crisis, 2008-2009.; BUSINESS & ECONOMICS -- Finance; Electronic books; Electronic books; Electronic books